Successful allogeneic stem cell transplantation of a patient with Werner syndrome and acute myeloid leukemia. (September 2021) - Fiegle, Eva; Crysandt, Martina; Bouillon, Anne-Sophie; Silling, Gerda; Elbracht, Miriam; Begemann, Matthias; Brümmendorf, Tim H.; Beier, Fabian; Jost, Edgar
Highlights: Werner syndrome is an adult-onset syndrome of accelerated aging predisposing to solid cancer and hematological malignancies. Chemotherapy and stem cell transplantation was successful in a patient with Werner syndrome and AML. Despite the poor risk profile, the patient remains in remission 5 years after transplantation and toxicity was acceptable.